The welfare analysis of congestion tax: case study of Jakarta, Indonesia - Suryo, Robin Asad, author; Fan, C. M., advisor; Fan, L. S., committee member; Weiler, Stephan, committee member; Olienyk, John, committee member (Colorado State University. Libraries, 2002)
Traffic congestion is a common phenomenon in many big cities including Jakarta, Indonesia. Economists have long advocated to reduce the congestion by using tax or price mechanism. The imposition of congestion tax will improve the efficiency of resource allocation. However, congestion tax also has negative impact on equity, in the meantime equity in transportation is very important. This dissertation evaluates the impact o f hypothetical congestion tax scenarios in the Central Business District (CBD) of Jakarta, Indonesia. The study shows that even though the tax has desirable effects on efficiency to travelers as a whole, it has negative impact on equity. The decomposition of welfare by income groups shows that the middle income travelers receive the highest benefits from the efficiency improvement, while the low income travelers benefit the least. Based on modal split auto drivers experience welfare improvement, while bus and motorcycle riders experience losses. By implementing cost-benefit criterion and assigning certain weights, we are not only able to make the impact of the tax to be progressive but also to increase the total utility or welfare received by travelers.
Keywords: traffic congestion; studies; polls and surveys; public transportation; roads and highways; questionnaires; transportation planning; traffic flow; prices; case studies; commuting; low income groups; copyright; travel; urban areas; automobile drivers